2000
DOI: 10.1111/j.1469-7793.2000.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

An oxygen‐, acid‐ and anaesthetic‐sensitive TASK‐like background potassium channel in rat arterial chemoreceptor cells

Abstract: The biophysical and pharmacological properties of an oxygen‐sensitive background K+ current in rat carotid body type‐I cells were investigated and compared with those of recently cloned two pore domain K+ channels. Under symmetrical K+ conditions the oxygen‐sensitive whole cell K+ current had a linear dependence on voltage indicating a lack of intrinsic voltage sensitivity. Single channel recordings identified a K+ channel, open at resting membrane potentials, that was inhibited by hypoxia. This channel had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
373
1
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(398 citation statements)
references
References 28 publications
17
373
1
7
Order By: Relevance
“…They produce background K + currents that are inhibited by external acidification and G-protein-coupled receptors (15) and activated by volatile anesthetics (16). Recent evidence suggesting that Task channels are inhibited by hypoxia comes from studies showing that the O 2 -sensitive background K + currents in carotidbody type I cells have electrophysiological and pharmacological properties of Task1 and Task3 (17)(18)(19).…”
mentioning
confidence: 99%
“…They produce background K + currents that are inhibited by external acidification and G-protein-coupled receptors (15) and activated by volatile anesthetics (16). Recent evidence suggesting that Task channels are inhibited by hypoxia comes from studies showing that the O 2 -sensitive background K + currents in carotidbody type I cells have electrophysiological and pharmacological properties of Task1 and Task3 (17)(18)(19).…”
mentioning
confidence: 99%
“…Those K 2P channels that form functional K ϩ channels exhibit interesting electrophysiological and pharmacological properties. For example, TASK-1 and TASK-3 are active at rest, highly sensitive to extracellular pH and oxygen concentration (22), and activated by volatile anesthetics (23,24). TREK-1 and TREK-2 are activated by free fatty acids, protons, increased membrane tension, heat, and volatile anesthetics (25,26).…”
mentioning
confidence: 99%
“…TASK3 is expressed at very low levels among the normal tissues except in the brain, where high levels expression of TASK3 were detected (7)(8)(9). The physiological functions of TASK channels are largely unknown, though their roles in the regulation of breathing (12,13), aldosterone secretion (5) and anesthetic-mediated neuronal activity (14) have been proposed. Recently, we showed that TASK3 is amplified in 10% of breast cancers and is overexpressed at a higher frequency of breast, lung, colon, and metastatic prostate cancers (15), suggesting that TASK3 may play a role in pathogenesis of some human carcinomas.…”
mentioning
confidence: 99%